2021
DOI: 10.1108/jcom-10-2020-0114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organizational conflict history and employees' situational perceptions of COVID-19 on negative megaphoning and turnover intention

Abstract: PurposeThis study explores the interaction effects of organizational conflict history and employees' situational perceptions of COVID-19 on negative megaphoning and turnover intention.Design/methodology/approachSurvey data (N = 476) were collected from US citizens, who self-identified as full-time employees, through Amazon Mechanical Turk (MTurk) in August 2020.FindingsOrganizational conflict history (i.e. highly conflict-prone vs less conflict-prone workplaces) interacts with employees' situational perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…More specifically, the results showed that, compared to the period before the pandemic, conflicts at school for both personal and work-related reasons were defused. This finding emphasizes, similar to related research (Chon et al, 2021;Lee & Kim, 2021), the positive contribution of crises in social organizations like schools, in that meaningful and honest feedback is provided while creative thinking is also fostered. This finding might also be credited, among other things, to the reduced number of multiple interactions among the school community members owing to distance teaching, the need to solve new problems concerning the school operation during the pandemic (educational, administrative), and the lack of playground supervision of a large number of students attending schools (≥ 200).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…More specifically, the results showed that, compared to the period before the pandemic, conflicts at school for both personal and work-related reasons were defused. This finding emphasizes, similar to related research (Chon et al, 2021;Lee & Kim, 2021), the positive contribution of crises in social organizations like schools, in that meaningful and honest feedback is provided while creative thinking is also fostered. This finding might also be credited, among other things, to the reduced number of multiple interactions among the school community members owing to distance teaching, the need to solve new problems concerning the school operation during the pandemic (educational, administrative), and the lack of playground supervision of a large number of students attending schools (≥ 200).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the issue of conflict management has been brought to the surface by research results from the wider field of social organizations (Cora, 2020;Chon et al, 2021;Mihaylova, 2020Mihaylova, , 2021Nadjafova, 2021). More specifically, relevant surveys have shown that during the COVID-19 pandemic the number of conflicts between staff members on the one hand was limited due to the physical distancing of employees and remote work, but on the other hand, their texture and content changed.…”
Section: Introductionmentioning
confidence: 99%
“…In short, Covid-19 was an unprecedented crisis, in which the role of internal communication as a tool for managing the ambiguity and uncertainty faced by employees was reinforced (Sun et al, 2021;Li et al, 2021). In this sense, the IC carried out during the pandemic prioritised the generation of trust in the organisation and its leaders through transparency and the use of emotional communication, as Chon, Tam and Kim (2021) argue. However, although communication executives perceived the opportunity to reclaim the strategic role of communication vis-à-vis top management, the efforts of organisations seem to have been oriented towards the reorganisation and coordination of remote work.…”
Section: Discussionmentioning
confidence: 99%
“…is evoked or if other influences, like advanced science and health communication training, override emotions and uncertainty. To further explore the role of external factors in communicators' decision-making in their management of pandemic communication with stakeholders, we ask:MethodPrevious scholars have conducted studies that investigated COVID-19, but those studies reviewed internal communications and used surveys to gain insights (e.g Chon et al, 2021; . Ecklebe and L€ offler, 2021;Einwiller et al, 2021;Heide and Simonsson, 2021;Yeomans and Bowman, 2021).…”
mentioning
confidence: 99%
“…With regard to managing the communication of COVID-19, one of the most severe infectious disease threats in recent world history, scholars recently researched the impact of COVID-19 on health communication practitioners (Gregory et al ., 2021), though studies have mainly used self-reporting and surveys (e.g. Chon et al ., 2021; Ecklebe and Löffler, 2021; Einwiller et al ., 2021). As a previous study indicated, health organizations and their public health information management decisions are influenced by different external factors (e.g.…”
mentioning
confidence: 99%